2011
DOI: 10.1074/jbc.m110.205062
|View full text |Cite
|
Sign up to set email alerts
|

The cAMP-responsive Rap1 Guanine Nucleotide Exchange Factor, Epac, Induces Smooth Muscle Relaxation by Down-regulation of RhoA Activity

Abstract: This study reports a new mechanism of cAMP mediated relaxation of Ca2+sensitized force, in smooth muscle (SM) through Epac, a GTP exchange factor for the small GTPase Rap1 which results in suppression of RhoA activity. We find that Epac selective cAMP analogue, 8‐pCPT‐2′‐O‐Me‐cAMP (007), significantly reduced agonist‐induced contractile force, in both intact and permeabilized vascular, gut and airway SM. Responses to 007 were independent of PKA and PKG. Activation of Epac resulted in increased Rap1·GTP accompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
93
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 66 publications
8
93
0
1
Order By: Relevance
“…Initial evidence for a role of EPAC, in particular EPAC1 in the regulation of vasorelaxation came from the observation that the EPAC agonist, 8-CPT and derived compounds directly relaxes several types of vascular smooth muscle preparations, for example cell preparation from rat aorta and pulmonary artery precontracted with endothelin. 55,56 Consistent with this finding, 8-CPT-induced relaxation is decreased in mouse vessels lacking a direct target of EPAC, Rap1B. 57 Of particular importance, Rap1B knockout mice develop hypertension, in part, via functional changes to VSMC and this indicates an essential role of Rap1 and possibly EPAC in maintaining normal vascular physiology.…”
Section: Regulation Of the Vascular Tonesupporting
confidence: 62%
See 2 more Smart Citations
“…Initial evidence for a role of EPAC, in particular EPAC1 in the regulation of vasorelaxation came from the observation that the EPAC agonist, 8-CPT and derived compounds directly relaxes several types of vascular smooth muscle preparations, for example cell preparation from rat aorta and pulmonary artery precontracted with endothelin. 55,56 Consistent with this finding, 8-CPT-induced relaxation is decreased in mouse vessels lacking a direct target of EPAC, Rap1B. 57 Of particular importance, Rap1B knockout mice develop hypertension, in part, via functional changes to VSMC and this indicates an essential role of Rap1 and possibly EPAC in maintaining normal vascular physiology.…”
Section: Regulation Of the Vascular Tonesupporting
confidence: 62%
“…62 Of particular importance, activation of EPAC-Rap1 signaling lowers VSMC contractility via the inhibition of the small GTPase RhoA activity, a master regulator of VSMC contraction and the dephosphorylation of myosin light chain ( Figure 5). 55,56 Conversely, in microvascular smooth muscle cells EPAC stimulates RhoA activity to increase the expression of functional α2C-ARs that mediate constriction of small blood vessels. 63 Altogether, these observations indicate that depending on the vascular bed, EPAC may induce vasorelaxation or vasoconstriction.…”
Section: Regulation Of the Vascular Tonementioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported the existence of a cross-talk between Rap1 and RhoA signaling pathways in vascular smooth muscle. Activation of Rap1 causes relaxation by decreasing the Ca 2ϩ sensitization of force in smooth muscle through downregulation of RhoA activity (588). Rap1 activation is triggered by the exchange factor Epac, activated by the rise in cAMP induced by the stimulation of vasorelaxing receptors such as ␤-adrenergic or prostglandine I 2 receptors.…”
Section: Ras Locus (H-ras-v12) (427) In Contrast H-rasmentioning
confidence: 99%
“…Surprisingly, the antispasmogenic activity of glucagon on carbachol-evoked contraction was unapparent after removal of the tracheal epithelium, clearly showing the crucial role of epithelial cells in this protective effect. This result was unexpected, once the elevation of intracellular cAMP levels leads to a relaxation of ASM (Zieba et al 2011, Billington et al 2013. To better explain this finding, we evaluated the expression of GcgR on both tracheal and lung tissue in mice from the A/J strain.…”
Section: Discussionmentioning
confidence: 99%